Resources and capabilities for logistics 4.0 and sustainable value creation: a study of logistics service providers in an emerging market - Vasiulis Ferreira Rodrigues, Nayra [UNESP]; De Camargo Fiorini, Paula [UNESP]; Piato, Éderson Luiz; Lopes de Sousa Jabbour, Ana Beatriz; Chiappetta Jabbour, Charbel Jose (Emerald, 2024)
Purpose: The present study aims to identify the resources and capabilities that enable logistics service providers (LSPs) to create sustainable value through Logistics 4.0. Design/methodology/approach: A multiple case study was conducted with five LSPs operating in an emerging market context. Data were analyzed using the content analysis technique with the support of NVivo software. Findings: Drawing on the resource-based view theory, the study elucidates the resources and capabilities necessary for the successful adoption of Logistics 4.0 by LSPs. The findings highlight the significance of integrating Logistics 4.0 technological resources with other organizational assets, including human capital, an innovative culture, leadership and strategic partnerships. This integration can enable companies to optimize the sustainable value derived from their digital transformation initiatives. Research limitations/implications: The present research focused on LSPs, potentially overlooking insights that could be gained from other segments of the supply chain. The study paves the way for future studies to examine resources and capabilities in a range of other supply chain management functions. Originality/value: The study offers unique theoretical and practical insights by identifying key resources for the adoption of Logistics 4.0 among LSPs, emphasizing its potential for sustainable value creation. It highlights the environmental, economic and societal impacts of 4.0 technologies, outlining the implications for policymakers to drive the successful adoption of Logistics 4.0 in emerging markets while also promoting social inclusion and professional development of logistics workers.
Keywords: Industry 4.0; Logistics service providers; Resourced-based view; Smart logistics; Sustainable supply chain